Flow of an Eyring-Powell Model Fluid between Coaxial Cylinders with Variable Viscosity. (20th November 2013) - Hussain, Azad; Malik, M. Y.; Khan, Farzana
Abstract : We consider the flow of Eyring-Powell model fluid in the annulus between two cylinders whose viscosity depends upon the temperature. We consider the steady flow in the annulus due to the motion of inner cylinder and constant pressure gradient. In the problem considered the flow is found to be remarkedly different from that for the incompressible Navier-Stokes fluid with constant viscosity. An analytical solution of the nonlinear problem is obtained using homotopy analysis method. The behavior of pertinent parameters is analyzed and depicted through graphs.